Antibiotic and Disinfectant Susceptibility Patterns of Bacteria Isolated from Farmed Fish in Kirinyaga County, Kenya - Daniel W. Wanja; Paul G. Mbuthia; Robert M. Waruiru; Lilly C. Bebora; Helena A. Ngowi; Philip N. Nyaga (International Journal of Microbiology)
Fish bacterial pathogens cause diseases which result in a considerable economic impact on the aquaculture industry, necessitating the use of antimicrobials for their control. However, intensive and indiscriminate use of antimicrobials has led to increased occurrence of drug resistance in pathogenic bacteria, as well as normal flora. The aim of the current study was to determine the susceptibility patterns of bacteria isolated from fish, with respect to some commonly used antibiotics and disinfectants. Bacteria were isolated between December 2017 and April 2018 from farmed Nile tilapia, African catfish, goldfish, and koi carp in Kirinyaga County, Kenya. Antibiotic and disinfectant susceptibility patterns of 48 isolates belonging to the genera Aeromonas, Proteus, Klebsiella, Citrobacter, Salmonella, Streptococcus, Pseudomonas, Escherichia, Serratia, and Micrococcus were established using the Kirby–Bauer disc diffusion method and agar well diffusion technique, respectively. The antibiotics evaluated included ampicillin, tetracycline, co-trimoxazole, streptomycin, kanamycin, gentamicin, co-trimoxazole, and chloramphenicol, while the disinfectants tested were quaternary ammonium compound, formalin, hydrogen peroxide, sodium hypochlorite, and iodine. All the bacteria except Micrococcus, Escherichia, and Salmonella species showed multiple drug resistance patterns. Streptococcus showed resistance to six antibiotics, while Proteus, Pseudomonas, and Serratia were resistant to five antibiotics. The multiple antibiotic resistance index ranged from 0.1 to 0.8, with Streptococcus spp. having the highest score value. All the organisms were sensitive to gentamicin, while co-trimoxazole and ampicillin showed the highest resistance at 73% (n = 34) and 62% (n = 31), respectively. Most of the disinfectants showed antibacterial activity with varying magnitudes. The isolates were 100% sensitive to hydrogen peroxide and formalin, but were resistant to sodium hypochlorite at recommended user-dilution. The study has shown that some of the bacterial isolates were resistant to common antibiotics and disinfectants; thus, it is recommended to include an antibiogram whenever making any therapeutic decision. The resistant bacteria may transmit resistance genes to other fish bacteria and also to human bacteria, thus making it difficult to treat the resultant disease(s); thus, there is a possibility that these resistant bacteria may be transmitted to humans who consume or handle the carrier fish. It is, therefore, advisable that fish are cooked properly before consumption, so as to kill bacteria that may be present.